PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR CAMAT TENAYAN RAYA DI PEKANBARU - Nanik Yuzalmi (Ensiklopedia of Journal, 2019)
The purpose of this study was to analyze the effect of supervision and work discipline on employee performance at the Tenayan Raya_ Pekanbaru District Office simultaneously and partially. This research is quantitative. The data collection method used in this study was through interviews, observation, and questionnaires. In this study, problem solving was carried out through validity and reliability tests, classical assumption tests, multiple linear regression tests, hypothesis testing (t test, f test, R2 test), all of which were seen using the SPSS (Statistical Product and Service Solution) version 20.0 program. The population that is the object of research is the employees of the Tenayan Raya Pekanbaru Sub-district Office, totaling 40 employees, and the sample used is all 40 employees. The result of the coefficient of determination (Adjusted R-Square) obtained is 0.854 or 85.4% of employee performance is influenced by the variables of supervision and work discipline, while the remaining 14.6 is influenced by other variables not examined by the researcher. From the results of multiple linear regression test shows Y = 3.633 + 0.832X1 + 0.103X2. From the results of the t-test, it is known that supervision has a significant effect on employee performance, with tcount greater than ttable, namely 12,900 > 2,026 and work discipline has a significant effect on employee performance, with tcount greater than ttable, ie 3,902 > 2,026. At a significant level of 0.05 from the Fcount test of 114,617, which is greater than the Ftable value of 3.24, this indicates that the proposed hypothesis is acceptable.Keywords: Supervision, Work Discipline, Employee Performance.